Energy of Surface Layer Deterioration of Copper-Based Materials under Dry Sliding with High Electric Current Density; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Fadin V. V.; Aleutdinova M. I.; Rubtsov V. E. Valery Evgenjevich; Aleutdinov K. A. (2016, 2016)
Title screen